Comparison of Dijkstra dan Floyd-Warshall Algorithm to Determine the Best Route of Train - Tri Setya Dermawan (IJID (International Journal on Informatics for Development), 2018)
This study aims to find out the comparison of Dijkstra and Floyd-Warshall algorithms in finding the best path on a train trip.  The best route is the path, which has the minimum price of a train journey. The results of route discovery will be displayed in a web-based application using the PHP programming language and MySQL database. The results of these two algorithms are compared using four parameters: time complexity, memory complexity, level of completion and level of optimization. Based on our experiments, Dijkstra algorithm has better performances on those four parameters than Floyd-Warshall algorithm.